Improving Students’ Writing Ability In Recount Text Through Comic Strips Media At Eighth Grade Students Of Smp Muhammadiyah 1 Tangunan - Yesyika Imanniar; Heru Wibowo; Ahmad Lutfi Amrozi (Universitas Islam Lamongan, 2022)
This research aimed to find out the improvement of the students’writing ability in recount text using comic strips media viewed from both generic structure and language use at eighth grade of SMP Muhammadiyah 1 Tangunan. The type of this research was a Classroom Action Research consisted of two cycles. The research subjects were the students of eighth grade in 2021/2022 academic with 20 students. The instruments of this research were writing test and observation sheet. The data analysis indicated that there were some significant achievements in writing after teaching them through Comic Strips Media. It was proved by the improvement of the students’ ability. The mean score in writing ability d-test was 56.82, in cycle I was 63.37 and in cycle II to get improvement 77.18. The students’ improvement from d-test to cycle I was 11.51%, cycle I to cycle II was 21.85%. Based on the data analysis above, it can be concluded that through Comic Strips Media can improve the students’ writing ability in recount text is significantly. The mean score in cycle II is higher than cycle I and the mean score of cycle I is higher than D-Test.